The influence of the Plotagon Story learning video media in improving student speaking skills in Payakumbuh State Islamic Senior High School 2 / Ta’tsîru Washîlati al-Fidyu Plotagun Story fî Tarqiyati Mahârah al-Kalâm lada al-Thullâbi fi al-Madrasati at-Tsânawiyati al-Islmaiyati al-Hukumiyati at-Tsâniyah Payakumbuh - Fitri, Aulia (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2023)
The study title is the effect of media plotagon story video the improve arabic speaking skill on students at MAN 2 Payakumbuh school. According to initial observation and the result of arabic speaking skill by students, shows that skills of students are quite limited in arabic speaking skill because they dont understand and dont get excited in arabic speaking skill and the media used by teacher is unable to influence the student’s perceptions of themselve. And teachers still use the tradisional way of learning. So, author tries to use in learning arabic speaking skill on students is plotagon story. The study has quantitative research methodology to show an increase arabic speaking skill. A type use research instrumens the observation and examination. The procedure this study is explain shape, grup determination, prepare sample, study, test for data requirements. It found than value of (4,256) higher (2,055). Finally, media plotagon story video has effect improve arabic speaking skill on students at MAN 2 Payakumbuh.